Kekerasan gender terhadap kaum perempuan dalam perspektif pancasila - Mubarok, Zakiy; Izam, Muhamad Nurul; Khoirunnaswah, Najwa Karima (Maliki Interdisciplinary Journal, 2024)
RIGHT are a concept that is inherent in individual humans. Meanwhile, human rights are a legal and normative concept which states that these rights are universal and apply whenever and wherever. Nowadays, there are still many violations related to human related to human rights. One of them is gender violence, especially gender violence against women. Gender violence can be interpreted as men’s efforts to maintain their power, especially over women. In this journal article, we use a conceptual method that link visual and diagrammatic concepts. The aim of this research is to determine the characteristics and behavior of gender violence against women. The summary of action to raise awareness that gender violence can have negative effects on oneself and the surrounding environment, both physically and mentally. Apart from that, as Indonesian citizens who have Pancasila as a state ideology, this research was made to make Indonesian citizens aware that acts of gender violence against women aren’t in line with the perspective of Pancasila as a state ideology.